2009
DOI: 10.1007/s00520-009-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of the experience of participating in a cancer-related clinical trial

Abstract: Clinical trial participation is a positive experience for many patients with cancer, although there are a number of associated practical and emotional challenges. Trial participants may benefit from closer follow-up from clinical trial staff, especially the treating doctor, assessment of support needs and help in re-evaluating the meaning of their trial participation if their initial hopes and expectations are not met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 12 publications
6
44
0
1
Order By: Relevance
“…As is well-known from literature on clinical trials, [13][14][15][16] patients enrolled themselves in research because they were out of options and valued the hope that experimental approaches might offer. Altruistic motivations were also present, 8 but this was in addition to and not instead of the hope for personal gain.…”
Section: [Dr-85]mentioning
confidence: 99%
See 1 more Smart Citation
“…As is well-known from literature on clinical trials, [13][14][15][16] patients enrolled themselves in research because they were out of options and valued the hope that experimental approaches might offer. Altruistic motivations were also present, 8 but this was in addition to and not instead of the hope for personal gain.…”
Section: [Dr-85]mentioning
confidence: 99%
“…[9][10][11][12] Further, in the research context and in the early stages of translation to clinical care, these results will be generated in patients with late-stage disease, where the value of hope is enhanced and patients face complex decisions about the pursuit of small but risky benefits. [13][14][15][16] Thus, delivering on the promise of personalized medicine raises questions about how best to address the needs of patients and their providers in the design and delivery of genomebased diagnostics. To date, however, social science research exploring the experiences of patients and physicians provides only partial insight.…”
Section: Introductionmentioning
confidence: 99%
“…The interviewees perceived research participation as an opportunity to "give something back" to the centre and to contribute to knowledge. As suggested by other researchers [6,15,17,19], interviewees perceived that participation could benefit them personally; it was anticipated that sharing their experiences with a research team would be personally therapeutic. In some cases, altruism was more important than a lack of perceived personal benefit.…”
Section: Discussionmentioning
confidence: 96%
“…After analysing who declined and who chose to participate in randomised psychosocial intervention studies, Boesen et al [18] concluded that people with less education and from poorer socioeconomic groups were more likely to refuse participation. Also, the opportunity to share experiences of serious illness in research is argued to relieve stress and empower patients by giving them a sense of purpose and self-worth [2,3] and control over their illness in spite of practical and emotional challenges [19]. In terms of participants' involvement, Wright et al [14] maintain that having participants as research collaborators/partners rather than subjects is a crucial feature of study design.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation